"Immunocytochemical expression of P53, PTEN, FAS (CD95), P16INK4A and HPV L1 major capsid proteins in ThinPrep cervical samples with squamous intraepithelial lesions". Issue 6 (1st June 2013) - Grapsa, D.; Frangou‐Plemenou, M.; Kondi‐Pafiti, A.; Stergiou, E.; Nicolopoulou‐Stamati, P.; Patsouris, E.; Chelidonis, G.; Athanassiadou, P.
<x xml:space="preserve">Abstract</x> The aim of this study was to further investigate the immunocytochemical expression of p53, PTEN, Fas, p16, and HPV L1 capsid proteins in cervical smears with low and high grade squamous intraepithelial lesions (LSIL and HSIL, respectively). A total of 92 ThinPrep cervical samples, comprising 11 cases of HSIL, 61 cases of LSIL, and 20 negative cases were studied by immunocytochemical methods. The results obtained in LSIL cases were correlated with the available follow up data. Abnormal p53, PTEN, or Fas expression was found in a subset of HSIL cases, while positive expression for p16 was significantly associated with the diagnosis of HSIL (P < 0.0001, P = 0.001, P < 0.0001, and P < 0.0001, respectively). Among cases positive for p16 expression, the staining pattern was weak in 88.9% of LSIL cases and strong in 80% of HSIL cases (P < 0.0001). The p16 negative/L1 positive and p16 positive/L1 negative staining patterns were significantly associated with the presence of LSIL and HSIL, respectively (P < 0.0001). None of these markers had a significant prognostic value in LSIL cases (P > 0.05). Our results suggest that loss of PTEN or Fas expression and p53 overexpression may be involved in the process of neoplastic transformation of the cervical epithelium. Furthermore, negative or weak immunocytochemical staining for p16 in a Pap smear may strongly argue against the presence of a high grade lesion, while the combined p16/L1 staining pattern may be useful as a diagnostic adjunct for differentiating between LSIL and HSIL. Diagn. Cytopathol. 2014;42:465–475. © 2013 Wiley Periodicals, Inc.